Composition analysis of soybean salt resistant mutants by raman spectroscopy and chemometrics - Yılmaz, Ayberk; Kabuk, Hayrunnisa Nur; Kaygısız, Ersin; Fausto, Rui; MERİÇ, SİNAN; AYAN, ALP; ATAK, ÇİMEN; ÇELİK, ÖZGE; ILDIZ, GÜLCE ÖĞRÜÇ (My University, 2019)
Soya seeds belonging to fourth generation mutants (M<i) of two different salt-tolerant soybeans (Alaem-7 cultivar (A7) variety and S04-05 (S) breeding line) together with the corresponding controls were studied by Raman spectroscopy, complemented by chemometrics methods, and compared with the data obtained by the ultraviolet-visible-near infrared (UV-Vis- NIR) reflectance spectroscopy standard method. It is shown that gamma irradiation caused significant changes in the lipid-to-protein ratio of the studied mutants of the two soybean varieties, compared to the corresponding control group. An increase in the lipid-to-protein ratio was observed in the case of the studied Ataem-7 variety mutants, while in the investigated S04- 05 breeding line mutants this ratio was found to reduce. The obtained results show that gamma irradiation can be offered as technique to enrich the mutant soybeans either in proteins or lipids, according to their desired application. Also, the observed increase in the intensity of the characteristic Raman bands of phenylalanine of S-mutants, compared to those appearing in the Raman spectra of the control samples, indicates an increase in the relative amount of this nutritionally relevant amino acid in the genetically modified plants’ seeds.Both Ward’s cluster analysis and principal component analysis (PCA) showed a clear discrimination between mutants and controls (see Figure), which is in accordance with the compositional information extracted from the Raman bands’ intensity analysis and reflectance spectroscopy measurements.